RESTLESS LEGS SYNDROME IN END STAGE RENAL DISEASE PATIENTS UNDERGOING MAINTENANCE HEMODIALYSIS: Restless Legs Syndrome - Jamal, Yousaf; Siddiqui, Umair Ahmed; Raza, Ahmed; Abbas, Kumail (Pakistan Armed Forces Medical Journal, 2014)
Objective: To study the frequency of restless legs syndrome in patients of end stage renal disease undergoing maintenance hemodialysis.Design: Cross sectional descriptive study.Place and Duration of Study: Department of medicine, CMH Multan from Nov 2010 to April 2011.Patients and Methods: One hundred and ninety four (n=194) patients of End stage renal disease who had been on maintenance hemodialysis for at least 3 months, were included in the study after full informed consent and using consecutive sampling. Patients having dementia, psychiatric illness, pregnancy, hypothyroidism, Parkinson’s disease and alcoholics were excluded from the study. Patients who fulfilled all four diagnostic criteria for restless legs syndrome as proposed by International restless legs syndrome study group (IRLSSG), by direct questioning were diagnosed as having restless legs syndrome.Results: The frequency of restless legs syndrome was found to be 12.4% in patients undergoing hemodialysis (10.5% in males versus 16% in females). The mean duration of hemodialysis was higher among RLS positive patients (12.88 ± 5.543 months) as compared to RLS negative patients (6.94 ± 4.610 months).Conclusion: RLS is a frequent, under-diagnosed co-morbidity in patients undergoing maintenance hemodialyis.